2022
DOI: 10.1108/jrit-12-2021-0086
|View full text |Cite
|
Sign up to set email alerts
|

Remote learning in the context of COVID-19: reviewing the effectiveness of synchronous online delivery

Abstract: PurposeThis article aims to explore student views from a UK higher educational institution about the concept of remote online higher educational delivery. Students were asked about opinions towards working remotely and the psychological impact this had upon students and students' studies. The research provided students with the opportunity to reflect upon whether the practice of delivering education remotely continues to provide students with a beneficial student learning experience.Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…Learners who are more attached to their instructor or the course often put more effort into subject learning and turn out to be more engaged (Kurt et al, 2022 ). However, not all learners have favourable attitudes towards online learning (Khlaif et al, 2021 ), and many prefer face-to-face (f2f) over online learning (Baxter & Hainey, 2022 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Learners who are more attached to their instructor or the course often put more effort into subject learning and turn out to be more engaged (Kurt et al, 2022 ). However, not all learners have favourable attitudes towards online learning (Khlaif et al, 2021 ), and many prefer face-to-face (f2f) over online learning (Baxter & Hainey, 2022 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…But unlike asynchronous online learning, engaging learners in SOL is even more challenging due to its lack of flexibility in time, pace, and duration (Park & Bonk, 2007 ). The condition is further aggravated by the increase in stress and anxiety brought about by the measures imposed to curb the pandemic outspread (Kee, 2021 ); and learners are likely to face technical hindrance (Bedenlier, et al, 2020 ) as well as undue distractions from their home environments (Baxter & Hainey, 2022 ). All these are some of the problems that need to be addressed when learning online synchronously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that online learning can be beneficial. Some participants found online remote learning useful for providing instant feedback, boosting motivation, and fostering a community of practice [6]. There is, however, a negative viewpoint associated with feelings of isolation, un-motivation, and a preference for face-to-face delivery (F2F).…”
Section: Introductionmentioning
confidence: 99%